Contextualizing a framework for improving postnatal care in Ethiopia - Elias Teferi Bala; Lizeth Roets (Frontiers Media S.A., 2022)
BackgroundPostnatal care is among the major recommended interventions to reduce maternal deaths. To improve the low postnatal care utilization in Ethiopia, the framework developed for this purpose in Kenya was contextualized and adapted for implementation in the Ethiopian context.ObjectivesThe objectives of this article are to share the process followed to contextualize Chelagat's framework for improving postnatal care, for the implementation in Ethiopia as well as the finalized contextualized framework.MethodsA quantitative descriptive research design was adapted. A self-administered questionnaire was used to gather data during November 2018 from 422 postnatal care providers and coordinators, using stratified random sampling. The AGREE II was utilized to assess adaptability and applicability and an open-ended question allowed to assess the challenges and opportunities for utilizing the framework. The data were analyzed using SPSS computer software, Version 23.ResultsThe findings revealed that the framework from Chelagat was adaptable to use for the improvement of postnatal care in the Ethiopian context. The results from the analysis of the data using AGREE II indicated an average domain score of 92%, for contextualization possibility.ConclusionThe framework originally developed by Chelagat was contextualized and refined to be implemented in Ethiopia to improve postnatal care.